Association between risk of preeclampsia and maternal plasma trimethylamine-N-oxide in second trimester and at the time of delivery - Xin Huang; Zuodong Li; Zhou Gao; Dapeng Wang; Xiaohui Li; Ying Li; Chunmei Mi; Jun Lei (BMC, 2020)
Abstract Background The data on the association between the microbiota-dependent metabolite trimethylamine-N-oxide (TMAO) during pregnancy and risk of preeclampsia (PE) is limited. Methods We, therefore, conducted a prospective nested case control study during Sep 2017 to Dec 2018 to examine the association between plasma TMAO measured during pregnancy and the risk of PE. Total of 17 patients diagnosed with early onset PE (EOPE), 49 with late onset PE (LOPE) and 198 healthy controls were enrolled. Blood samples were collected at 15-23 weeks gestation and time at delivery. The Logistic regression model was used to assess the odds ratio (OR) and 95% confidence interval (CI) for TMAO and risk of PE, EOPE, LOPE, mild PE, and severe PE. Results We found that the mean TMAO levels of overall subjects in the second trimester (T2) and at the time of delivery (TD) were 90.39 μg/m3 (standard deviation (SD) =45.91) and 175.01 μg/m3 (SD = 160.97), respectively. No significant spearman correlation was found between the TMAO in those two periods (p > 0.05). T2 TMAO was not significantly associated with risk of PE or risk of any PE subtypes (p > 0.05). However, TD TMAO was significant associated with risk of PE, EOPE and severe PE (adjusted OR and 95%CI were 1.24(1.09, 1.40), 1.62(1.29, 2.03), and 1.41(1.17, 1.70)) per 50 μg/m3 increment, respectively). Conclusion Our study found that plasma TMAO level would alter over the course of pregnancy. The major role of TMAO in PE development might be in the accelerating process not in the initiation.